Three dimensions of open innovation 2 - Menendez, Marisol (Henry Stewart Talks, 2021)
POP K, The “Areas Involved in OI Process” Canvas, The mystery of the disconnected organization, The “KPI Mapping” Canvas, The mystery of the opposed KPIs, The “Collaboration Mapping” Canvas, The mystery of trust, Mindset alignment